Reinjury after acute lateral ankle sprains in elite track and field athletes - Malliaropoulos, N.; Ntessalen, M.; Papacostas, E.; Longo, U. G.; Maffulli, N. (The American Journal of Sports Medicine, 2009)
Lateral ankle sprains can lead to persistent disability in athletes. The authors studied the effect of a lateral ankle sprain on reinjury occurrence in the same region.